2005
DOI: 10.1007/s11274-004-4798-0
|View full text |Cite
|
Sign up to set email alerts
|

Micro-encapsulation of Bifidobacterium lactis for incorporation into soft foods

Abstract: Micro-encapsulation of the probiotic micro-organism Bifidobacterium lactis isolated from a bio-yoghurt starter culture, was carried out using a mixture of hydrated gellan and xanthan gums. Rheological studies showed that the gum mix was suitable for encapsulation of B. lactis, for incorporation into soft foods/beverages. The gel behaved as a non-Newtonian material, and the flow curve fitted well to the Herschel-Bulkley model. The average yield stress of the gum was 1.515 Pa, indicating gum stability, and the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 11 publications
(25 reference statements)
2
23
0
1
Order By: Relevance
“…Microcapsule size distributions with a very wide range have been reported by several researchers and the optimum microcapsule size is a compromise between the effectiveness of encapsulation and the sensory properties (Arup et al, 2011). A minimum diameter of 100 m has been suggested to offer better protection in gastric juice, and an optimum range of 100-200 m has been proposed (McMaster, Kokott, & Slatter, 2005). The mean diameter of our emulsification/internal gelation beads was just within this limit.…”
Section: Size and Size Distribution Of The Beads Prepared By Both Tecmentioning
confidence: 70%
“…Microcapsule size distributions with a very wide range have been reported by several researchers and the optimum microcapsule size is a compromise between the effectiveness of encapsulation and the sensory properties (Arup et al, 2011). A minimum diameter of 100 m has been suggested to offer better protection in gastric juice, and an optimum range of 100-200 m has been proposed (McMaster, Kokott, & Slatter, 2005). The mean diameter of our emulsification/internal gelation beads was just within this limit.…”
Section: Size and Size Distribution Of The Beads Prepared By Both Tecmentioning
confidence: 70%
“…Higher than 10 6 cfu mL −1 (McMaster et al, 2005) Sodium alginate with poly-L-lysine or chitosan (Extrusion technique)…”
Section: Bifidobacterium Lactismentioning
confidence: 99%
“…Gellan gum is a microbial polysaccharide derived from Pseudomonas elodea and is constituted of a repeating unit of four monosaccharide molecules (glucose, glucuronic acid, glucose and rhamnose). Several investigations have reported the combination of gellan and xanthan as microencapsulating materials (Muthukumarasamy et al, 2006;McMaster et al, 2005). The combination of xanthan and gellan gums to form bead is not only acid resistant but also is stabilized by calcium ions which may protect probiotic cells from acid injury.…”
Section: Miscellaneous Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Faergemand et al (1997) found that incubation of sodium caseinate with TGase only slightly influences its emulsifying properties. The optimal size for microcapsules containing probiotics depends, however, on the intended purpose and on the type of food (McMaster et al, 2005). While 1% capsules with diameters between 2 and 3 mm could not be sensorily detected in salami , capsules of that size range give an adverse sensorial effect in yoghurt, milk and sour cream (Hansen et al, 2002).…”
Section: Formation and Characterization Of Casein Capsulesmentioning
confidence: 99%